The Legitimacy of Religion and Power: A Study of the Transformation of the Safavid Dynasty from Order to State - Ahmad Zaim Muchlisi A’la; Fadil SJ (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study analyzes the transformation of the Safavid Dynasty from a Sufi order into an institutionalized state, with religious legitimacy positioned as a central factor in the formation and consolidation of political power. It aims to demonstrate that religion functioned not only as a belief system but also as a strategic instrument for establishing authority within a premodern socio-political context. This study employed a qualitative approach with a historical-analytical design, using secondary data derived from classical works, academic books, and journal articles. The analysis was conducted using Max Weber’s theory of legitimacy and a political theology approach. The findings indicate that, in its early phase, the Safavid Order relied on religious charismatic authority. Over time, this authority developed into a more structured political power system, particularly under the leadership of Ismail I. The establishment of Twelver Shiism as the official state ideology became a key factor in fostering social integration, strengthening political legitimacy, and shaping a distinctive collective identity. Religious legitimacy was not merely symbolic but was systematically institutionalized through educational, legal, and administrative structures, enabling the continuity of political stability despite internal and external challenges. The study concludes that the Safavid transformation demonstrates how religious legitimacy can operate as an integrative force linking spiritual authority, political structures, and social cohesion in the formation of a sustainable state. These findings contribute to historical and political theology studies by clarifying the role of religious legitimacy in the institutionalization of power in premodern Islamic governance.